The Gap Between Worlds: A Tactile Ceramic Experience of Sound from a Deaf Perspective - Sabmeethavorn, Thanatira (Auckland University of Technology, 2023)
I identify as both a deaf and hard-of-hearing person; yet I am neither because I occupy a space in-between. People assume that deaf individuals live in silence. However, I perceive the worlds of the hearing and d/Deaf as fragmented spaces due to a cochlear implant which acts as a threshold, allowing me to cross between worlds without a second thought. This research is a personal response to the question, " How can textile practice demonstrate my experience of being between two worlds: d/Deaf and hearing?" This practice-based research project aimed to navigate my hearing loss through ceramics, recognised as textile practice. Using action research as a guiding methodology, the gaps experienced in verbal communication are explored. This gap in communication is how I experience lipreading and hearing in my day-to-day life and prompted an investigation through a series of interactions with ceramic materials. Reflecting on my relationship with deafness, I have traced pieces of my struggles where my liminal position created a new dynamic; the gaps are illegible and there is a constant barrier between communication that I can never comprehend. To express my liminal positioning, repetitive hand-crafted making methods generate an interactive ceramic experience. The gaps, while they do not speak for themselves, serve as visual expressions that convey my situation between two worlds.